Costly self-insurance of rights offerings - DUONG, Truong Xuan (Institutional Knowledge at Singapore Management University, 2015)
We study how the underwriting decision of an equity rights offering is affected by the risk of offering failure. Firms can reduce failure risk by getting underwriting or by self-insuring through subscription price discounts and subscription precommitments. Self-insurance is generally regarded to be relatively costless, but we provide evidence from Singapore that is consistent with the existence of implicit costs. In particular, the existence of self-insurance costs implies that firms with better projects will have larger discounts and that firms with higher ownership concentration will have more precommitments. Hence, our results support costly self-insurance against issue failure as a factor in explaining the rights issue paradox.